On the Origins of the Fleming-Mundell Model - Boughton, James (Washington, D.C. : International Monetary Fund, 2002)
Forty years ago, Marcus Fleming and Robert Mundell developed independent models of macroeconomic policy in open economies. Why do we link the two, and why do we call the result the Mundell-Fleming, rather than Fleming-Mundell model?.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Italy